A Systematic Thematic Review of Task-Based Language Teaching for Young Learners - Nahian Ahmed Ananna (Universitas Islam Negeri Palopo, 2026)
Task-Based Language Teaching (TBLT) has become very popular for young learners. However, it is not consistently or effectively used in the classroom. The present study is a systematic thematic review of the literature on TBLT for young learners. This study is designed to explore the ways in which children participate in task-based activities in primary English lessons and, ultimately, which type of tasks is most effective in supporting children's communicative language use, which in turn will lead them towards communicative language teaching. Focusing on 40 peer-reviewed studies that are published between 2015 and 2025, a qualitative thematic review has been carried out. The empirical study was only taken in classroom-based TBLT with young EFL learners that fulfilled strict criteria. Some themes were identified in task design, input-based instruction, interactional patterns, learner motivation, implementation challenges, and finally assessment and technology. Results highlight that engaging, hands-on, meaningful activities, and cooperative communication and interaction stimulate engagement, vocabulary development, and willingness to communicate in young learners. However, tasks that are too early, too production-oriented, and test-oriented can limit participation and cause anxiety, which can increase their affective filter. Emotional safety, peer support that is structured, and opportunities to repeat tasks are also noted as important, as these can enable children to experiment with language without stress, judgement, and fear of failure. The theme of adaptation of tasks to larger, exam-oriented classes is used particularly to address this point, which is often found in many EFL settings. The results also indicate that the design of tasks, organization of the classroom, and assessment methods of teachers should be in line with TBLT principles in learning. Therefore, providing developmentally appropriate environments with tasks and non-judgmental environments is critical to ensure the long-term success of young learners in English and in their everyday language.